2021
DOI: 10.3389/fcell.2021.756560
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lncRNA and mRNA Expression Profile in Relapsed Graves’ Disease

Abstract: Background: Graves’ disease (GD) is a common autoimmune disease, and its pathogenesis is unclear. Studies have found that the occurrence of GD is related to the immune disorder caused by the interaction of genetic susceptibility and environmental factors. The CD4+ T cell subset is closely related to the immune disorder of GD. LncRNAs are RNA molecules with a length of more than 200 nt and are involved in a variety of autoimmune diseases. However, the roles of lncRNAs in recurrent GD are still elusive. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“… a Functional enrichment analysis was performed with an integrative method that discovers significantly enriched pathways, across multiple datasets such as DisGeNET [ 22 ], Clinical Variations [ 24 ], DisGeNET [ 25 ], BeFree [ 26 ], BioCyc [ 27 ], KEGG [ 28 ], and MSigDBBioCarta [ 30 ]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Functional enrichment analysis was performed with an integrative method that discovers significantly enriched pathways, across multiple datasets such as DisGeNET [ 22 ], Clinical Variations [ 24 ], DisGeNET [ 25 ], BeFree [ 26 ], BioCyc [ 27 ], KEGG [ 28 ], and MSigDBBioCarta [ 30 ]. …”
Section: Resultsmentioning
confidence: 99%
“…To gain insights into the biological processes and molecular functions related to the targeted immune hubs in glioma, several analyses were conducted using multiple datasets such as DisGeNET [ 32 ], Clinical Variations [ 24 ], DisGeNET [ 25 ], BeFree [ 26 ], BioCyc [ 27 ], KEGG [ 28 ], and MSigDBBioCarta [ 30 ]. ToppGene and the clusterProfiler package were used to perform GO analysis and KEGG analysis to uncover enriched pathways across multiple datasets [ [33] , [34] , [35] ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al found that n335641, n337845, and TCONS_00022357-XLOC_010919 may participate in the proliferation and survival of B cells in GD [ 21 ]. Yao et al focused on relapsed GD patients and found that three downregulated lncRNAs (NONHSAT093153.2, NONHSAT118924.2, and NONHSAT209004.1) were closely related to the recurrence of GD [ 15 ]. In the present study, we found a signature profile of numerous dysregulated lncRNAs (27,354 upregulated lncRNAs and 10,329 downregulated lncRNAs) in PBMCs from GD patients compared with normal controls by sequencing technology.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has suggested that many lncRNAs are involved in the pathogenesis of autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus, and Hashimoto's thyroiditis [ 12 14 ]. Although the lncRNA profiles in CD4 + T cells of relapsed GD have been preliminarily investigated [ 15 , 16 ], the dysregulated lncRNAs in peripheral blood mononuclear cells (PBMCs) from GD patients and their potential functions remain poorly understood. Here, the present study is aimed at investigating the potential roles of lncRNAs in PBMCs from patients with GD.…”
Section: Introductionmentioning
confidence: 99%